Knowledge Translation Strategy to Reduce the Use of Potentially Inappropriate Medications in Hospitalized Elderly Adults. Issue 12 (2nd September 2016) - Cossette, Benoit; Bergeron, Josée; Ricard, Geneviève; Éthier, Jean‐François; Joly‐Mischlich, Thomas; Levine, Mitchell; Sene, Modou; Mallet, Louise; Lanthier, Luc; Payette, Hélène; Rodrigue, Marie‐Claude; Brazeau, Serge
Abstract : Objectives: To evaluate the effect of a knowledge translation (KT) strategy to reduce potentially inappropriate medication (PIM) use in hospitalized elderly adults. Design: Segmented regression analysis of an interrupted time series. Setting: Teaching hospital. Participants: Individuals aged 75 and older discharged from the hospital in 2013/14 (mean age 83.3, 54.5% female). Intervention: The KT strategy comprises the distribution of educational materials, presentations by geriatricians, pharmacist–physician interventions based on alerts from a computerized alert system, and comprehensive geriatric assessments. Measurements: Rate of PIM use (number of patient‐days with use of at least one PIM/number of patient‐days of hospitalization for individuals aged ≥75). Results: For 8, 622 patients with 14, 071 admissions, a total of 145, 061 patient‐days were analyzed. One or more PIMs were prescribed on 28, 776 (19.8%) patient‐days; a higher rate was found for individuals aged 75 to 84 (24.0%) than for those aged 85 and older (14.4%) ( P < .001), and in women (20.8%) than in men (18.6%) ( P < .001). The drug classes most frequently accounting for the PIM were gastrointestinal agents (21%), antihistamines (18%), and antidepressants (17%). An absolute decrease of 3.5% ( P < .001) of patient‐days with at least one PIM was observed immediately after the intervention. Conclusion: A KT strategy resulted in decreased use of PIM in elderly adults in the hospital. Additional interventions will be implemented to maintain or further reduce PIM use.